The Employment situation in Latin America and the Caribbean : employment formalization and labour income distribution (United Nations/ILO SantiagoCL, 2014)
Examines the employment situation in Latin America and the Caribbean.Explores several mechanisms that are playing a part in this picture, using an analysis of data for the period 2009-2013.
Keywords: EMPLOYMENT